The verdict is in: how did they decide? Using drivers' self-reported data to understand officers' decision making during traffic stop encounters. Issue 4 (20th April 2020) - Boateng, Francis D.; Howley, Caitlin
ABSTRACT: In the United States, traffic stop is the most common form of police-citizen encounter, and for many citizens, it is the only way they will ever interact with the police. The frequency of traffic stop encounters has therefore attracted a significant research interest. In the past several years, researchers have attempted to explain the dynamics of these interactions, with the hope to change attitudes and influence policy formation. To supplement the efforts of previous researchers, the current effort analyzed self-reported data from citizens to understand police decision making at three decision points during traffic stop encounters. Specifically, the present study aims to answer three questions: what variables predict whether an officer will let a citizen go without doing anything or decide to do something? If the officer decides to do something, what influences the officer's decision to choose an outcome over others? What are the drivers of use of force in traffic stop encounters? Results from the regression models suggest that reasons for the stop, verbal assault, officer and suspect characteristics are important predictors of police decision making behavior during traffic stop interaction. The findings have serious implications for developing better police-citizen relationships as well as improving public attitudes toward the local police.